Clinical study of repetitive transcranial magnetic stimulation to improve chronic pain after total knee arthroplasty - Wang Hongbin; Yuan Hua; Sun Xiaolong; Xu Mulan; Wu Xiangbo; Long Hua (康复学报)
ObjectiveTo investigate the effect of repeated transcranial magnetic stimulation(rTMS)on chronic pain after total knee arthroplasty(TKA).MethodsA total of 121 patients with postoperative chronic post-surgical pain(CPSP)who underwent unilateral TKA from January 2021 to June 2023 and who fulfilled the criteria were randomly assigned to receive rTMS(paralateral M1 area,10Hz,80% resting threshold,stimulation time of 1s,interval time of 3s,1200 pulses/min,once daily)or sham stimulation for one week.NRS scores and HSS scores for knee pain were compared between the two groups after 3 days,1 week,2 weeks,and 4 weeks of treatment,by repeated-measures analysis of variance.ResultsRepeated analyses of the NRS scores and total HSS scores in the two groups revealed statistically significant differences in rTMS compared with controls in pain (HSS1), joint activity (HSS3), flexion (HSS5), and subtraction (HSS7).ConclusionAs a safe and cost-effective neuromodulatory technique, rTMS is well suited to relieve chronic pain after TKA, improve the overall recovery of joint function, and improve quality of life, and is worthy of clinical application.